Development Prospects of Financial Social Network in Russia - A. V. Zolotaryuk; P. S. Kachibaya; A. N. Mityushenkov (Мир новой экономики)
The article describes the project for the establishment of financial social network in Russia, focused on the solution of small and medium-sized businesses’ financial problems. In the text article determines the overall structure of the project, reveals the stages of implementation and the main aspects of functioning. The effectiveness of the project is getting grounded, - as for the growth of the national economy, and same for the entrepreneurs.